SURFACE MODIFICATION OF SEMICONDUCTOR THIN FILM OF TiO2 ON GRAPHITE SUBSTRATE BY Cu-ELECTRODEPOSITION - Fitria Rahmawati; Sayekti Wahyuningsih; Nurani Handayani (Indonesian Journal of Chemistry, 2008)
Surface modification of graphite/TiO2 has been done by mean of Cu electrodeposition. This research aims to study the effect of Cu electrodeposition on photocatalytic enhancing of TiO2. Electrodeposition has been done using CuSO4 0,4 M as the electrolyte at controlled current. The XRD pattern of modified TiO2 thin film on graphite substrate exhibited new peaks at 2θ= 43-44o and 2θ= 50-51o that have been identified as Cu with crystal cubic system, face-centered crystal lattice and crystallite size of 26-30 nm. CTABr still remains in the material as impurities. Meanwhile, based on morphological analysis, Cu particles are dissipated in the pore of thin film. Graphite/TiO2/Cu has higher photoconversion efficiency than graphite/TiO2.